Phylogenic analysis of additional Neurospora crassa isolates - Tanja Radic; Silvia Gastaldello; Julia Diegmann; Till Roenneberg (Fungal Genetics Reports, 2012)
The ascomycete Neurospora crassa is classical model organisms in biology. So far, a phylogenetic analysis based on genomic sequences of four non-functional nuclear loci has been reported for 44 natural isolates of N. crassa. Three subgroups (clades) with a distinct geographical distribution have been identified: clade A (Caribbean Basin and Ivory Coast), clade B (Europe, Ivory Coast and India), and clade C (India). Here, we report the results of a phylogenetic analysis of 16 additional isolates. Six of these were from the Caribbean Basin, eight from Europe and one from Pakistan and one from Thailand. The previously described clades and their geographical distribution were generally confirmed. All Caribbean isolates belonged to clade A and all European isolates belonged to clade B, with the exception of one isolate from Italy, which also belonged to clade A, suggesting a transport from the Caribbean Basin or the Ivory Coast to Europe. Interestingly, the isolates from Pakistan and Thailand were found in a separate group, basal to all other clades. Their phylogenetic classification is not yet clear as they might belong to N. crassa but as well to N. perkinsii, potentially representing yet undescribed phylogenetic groups or species of Neurospora, or hybrids.